History of Japanese Writing System; From Kanji Into Hiragana - Limantoro, Gray Hansen; Atma, Yeyen Dwi (International Journal of Multidisciplinary Sciences and Arts, 2024)
The Japanese writing system has undergone a long and complex evolution since the introduction of Chinese characters (hànzì) in the 5th century. Over time, this system, comprising kanji, kana (hiragana and katakana), and romaji, has seen continuous transformations. This research explores the historical progression of the Japanese writing system, tracing its development from the early use of kanji and the adaptation of Man’y?gana to the eventual creation of kana. Kanji, originally imported from China, initially posed challenges due to its complexity and the mismatch with the Japanese language structure. As a result, Man’y?gana, an early form of Japanese script using kanji phonetically, emerged as an intermediary step. Eventually, this evolved into two distinct syllabaries: hiragana and katakana, collectively known as kana, which simplified writing and better suited the Japanese linguistic context. This study utilizes desk research to analyze the key stages of this transformation, focusing on the cultural, linguistic, and social factors that contributed to each phase of development. From the influence of Chinese characters to the creation of a uniquely Japanese writing system, the transition from kanji to kana reflects the need for reform and adaptation. By examining these historical shifts, the research sheds light on how Japan tailored a borrowed writing system to suit its own language and facilitated easier, more accessible written communication.